Case report: A case with atypical presentation oftesticular choriocarcinoma - Zhong, Bin; Zhang, Tao; Dong, Yi; Yin, Wei; Zhang, Jian-Xin; Jin, Wei-Dong (Frontiers in Oncology, 2024)
Testicular choriocarcinoma is a relatively rare malignancy with a highly aggressive nature. Timely diagnosis and treatment can help prolong the survival of patients and even cure them. This case reports a 29-year-old male who presented to the clinic for a month with epigastric pain. On examination, a massive mass of approximately 9*10 cm could be palpated in the upper abdomen. When asked about his previous history, the patient only described a history of a right inguinal hernia that had been repaired 12 years earlier. The admission diagnosis was considered the retroperitoneal tumor, which was found to have metastasized to the liver and lungs after the completion of relevant tests. We then performed a CT-guided lune puncture biopsy on day 8 of admission. The biopsy pathology suggested metastatic cancer was considered. As the symptoms of tumor compression gradually worsened, we performed surgical treatment (retroperitoneal tumor resection + partial duodenal resection + enteroanastomosis) on day 13 of admission. The postoperative pathology was choriocarcinoma. We subsequently conducted a detailed inquiry with the patient's family about his medical history and found a history of inguinal testicle. Through testicular ultrasound examination, it was preliminarily determined to be testicular choriocarcinoma (not yet pathologically confirmed). We wanted to start salvage chemotherapy as soon as possible after surgery. However, the patient's postoperative condition was poor, with rapid progression of hepatopulmonary metastases and gradually increased thyrotoxicosis, and we started salvage chemotherapy (EP regimen: etoposide and cisplatin) on postoperative day 12. However, the patient was forced to stop due to a severe chemotherapy reaction and died of respiratory and cardiac arrest in the hospital.For male patients with retroperitoneal mass, the possibility of germ-cell neoplasm should first be excluded. By inquiring in detail about a history of cryptorchidism and in the initial days of hospitalization, testicular exploration, ultrasounds, and serum tumor markers (AFP, β-HCG) tests can be conducted to rule out the possibility of germ-cell neoplasm, thereby preventing misdiagnosis and treatment delays. If the clinical diagnosis is metastatic germ-cell tumor with severe symptoms of metastatic disease, surgery should never be used as the initial treatment.